2018
DOI: 10.1016/j.gaitpost.2018.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Objective measures of unobstructed walking and obstacle avoidance in Parkinson’s disease subtypes

Abstract: PIGD subtype patients showed worse modifications in objective measures of unobstructed walking and obstacle avoidance. The observed modifications may contribute to increased fall occurrence in PIGD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Moreover, the stance phase is related to the stability of walking. [30][31] In the current study, we observed changes of gait parameters of healthy individuals under ETAAC conditions during walking. The results revealed that, in the walking cycle, the percentage of stance phase in the ETAAC condition (59.151 ± 1.903)% was significantly lower than in the HTAAC condition (59.825 ± 1.495)% (P < 0.05), while the percentage of single support phase in the ETAAC condition (40.726 ± 1.808)% was significantly higher than in the HTAAC condition (39.986 ± 1.250)% (P < 0.05).…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, the stance phase is related to the stability of walking. [30][31] In the current study, we observed changes of gait parameters of healthy individuals under ETAAC conditions during walking. The results revealed that, in the walking cycle, the percentage of stance phase in the ETAAC condition (59.151 ± 1.903)% was significantly lower than in the HTAAC condition (59.825 ± 1.495)% (P < 0.05), while the percentage of single support phase in the ETAAC condition (40.726 ± 1.808)% was significantly higher than in the HTAAC condition (39.986 ± 1.250)% (P < 0.05).…”
Section: Discussionmentioning
confidence: 69%
“…Gait characteristics of crossing step for both more affected (MAS) and less affected (LAS) limbs of PD group and both dominant limb (DL) and non-dominant limb (NDL) of control group (CG). www.nature.com/scientificreports www.nature.com/scientificreports/ parameters compared to a control group during single obstacle 23,24 and double obstacle conditions 20 . However, these studies did not analyze the differences between lower limb preferences and obstacle crossing role -leading and trailing limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 25% of people with PD (PwP) have unstable posture at diagnosis ( Kohat et al, 2021 ), and the incidence increases with time from diagnosis ( Kohat et al, 2021 ) often with the development of freezing of gait (FOG) ( Ge et al, 2020 ). This is associated with a shorter stride length ( Nanhoe-Mahabier et al, 2011 ; Orcioli-Silva et al, 2018 ). These changes have been linked to cognitive dysfunction and anxiety ( Giladi and Hausdorff, 2006 ; Weiss et al, 2015 ; Kueper et al, 2017 ; Yao et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%